1997
DOI: 10.1111/j.1439-0485.1997.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

The Amphipod Community as a Bioindicator in Algeciras Bay (Southern Iberian Peninsula) Based on a Spatio‐Temporal Distribution

Abstract: The amphipod population associated with Bugula nerilina (L.), a very common bryozoan species in Algeciras Bay (Strait of Gibraltar), was studied on a spatio-temporal scale, in order to define its role as a bioindicator. Samples were collected in December, March, June and September along a transect running from the external to the internal sampling stations.Fifty-three species belonging to 22 families were identified; the most abundant species were Jmsa marrnorata HOLMES, Ischyrocerus inexpectatus (RUFFO) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 20 publications
2
57
0
2
Order By: Relevance
“…Conradi et al 1997;Sánchez-Moyano and García-Gómez 1998;Guerra-García and García-Gómez 2001;Ohji et al 2002;Dauvin and Ruellet 2007). On the other hand, C. elongata is one of the most important algae in the intertidal ecosystems (Pérez-Cirera and Maldonado 1982;Guerra-García et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conradi et al 1997;Sánchez-Moyano and García-Gómez 1998;Guerra-García and García-Gómez 2001;Ohji et al 2002;Dauvin and Ruellet 2007). On the other hand, C. elongata is one of the most important algae in the intertidal ecosystems (Pérez-Cirera and Maldonado 1982;Guerra-García et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Chavanich and Wilson 2000;Thiel 2002;Castellanos et al 2003;De Broyer et al 2003;Chiesa et al 2005;Winfield et al 2006;Myers and Lowry 2009). Nevertheless, research has not been so intensive in the Iberian Peninsula, and the knowledge in this field is still fragmentary (Bellan-Santini and Ruffo 1998;Guerra-García et al 2009b, c, d) and mainly focused on the Strait of Gibraltar (Conradi et al 1997;Castelló and Carballo 2001;Guerra-García and Takeuchi 2002). However, there has been a slight increase in the interest of this region during the last decade (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Conradi et al (1997) showed that the amphipod population associated with the bryozoan Bugula neritina had a higher diversity and species richness in the stations located at the mouth of the bay than the inner stations with low water movement and higher sedimentation. Sánchez-Moyano and García-Gómez (1998) and Sánchez-Moyano et al (2002a, b) studied the spatiotemporal distribution of the epifaunal community of macrofauna living on the alga Halopteris scoparia, collected by scuba in several stations of Algeciras Bay, and reported that in the external zone a greater number of species appeared.…”
Section: Distribution Of Fauna and Algaementioning
confidence: 99%
“…It is an important industrial area, with chemical factories, refineries, thermal power plants, iron works, paper mills and ship yards, along with a major port (Conradi et al, 1997). Recently, several studies have been conducted in Algeciras Bay using subtidal benthic communities as bioindicators (sponges: Carballo et al, 1996;ascidians: Naranjo et al, 1996; epifauna of algae and briozoa: Conradi et al, 1997, Sánchez-Moyano andGarcía-Gómez, 1998;Sánchez-Moyano et al, 2000a, b, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Amphipods are important food sources for higher level predators such as fishes (Bell and Harmelin-Vivien, 1983;Pinnegar and Polunin, 2000) and possibly decapods (Lepoint et al, 2000;Vizzini et al, 2002). They are also sensitive to anthropogenic and natural disturbances (Conlan, 1994;Thomas, 1993) and are widely considered good potential indicators of ecosystem degradation (Conradi et al, 1997;Guerra-García and García-Gómez, 2001), notably in P. oceanica meadows (Sánchez-Jerez et al, 2000). These meadows, characterized by large heterogeneity at small and medium scales (Balestri et al, 2003;Gobert et al, 2003;Panayotidis et al, 1981;Zupo et al, 2006), could influence variability of amphipod assemblages.…”
Section: Introductionmentioning
confidence: 99%